Réponses

Meilleure réponse !
  • Utilisateur Brainly
2014-10-08T21:53:55+02:00
A= - 5 - (2,7 - 5) + (- 2,3 + 5,7)
A= - 5 - (- 2,3) + (+ 3,4)
A= - 5 + 2,3 + 3,4
A= - 5 + 5,7
A= 0,7

B= - 10 - (- 3,3 - 4,7) - (3,5 - 5)
B= - 10 - (- 8) - (- 1,5)
B= - 10 + 8 + 1,5
B= - 10 + 9,5
B= - 0,5

C= (- 3,9 + 5 ) + ( 7 - 10,5 ) - (- 3 - 1,4)
C= 1,1 + (- 3,5) - (- 4,4)
C= 1,1 - 3,5 + 4,4
C= 5,5 - 3,5
C= 2
il y a 1 probleme avec la repnse a
Non
on actualise comment ? stp
F5 sur ton ordi
merci :) encore tes trop gentil
2014-10-08T22:15:56+02:00
A = - 5 - (2,7 - 5) + (- 2,3 + 5,7)
A = - 5 - (- 2,3) + (+ 3,4)
A = - 5 + 2,3 + 3,4
A = - 5 + 5,7
A = 0,7

B = - 10 - (- 3,3 - 4,7) - (3,5 - 5)
B = - 10 - (- 8) - (- 1,5)
B = - 10 + 8 + 1,5
B = - 10 + 9,5
B = - 0,5

C = (- 3,9 + 5 ) + ( 7 - 10,5 ) - (- 3 - 1,4)
C = 1,1 + (- 3,5) - (- 4,4)
C = 1,1 - 3,5 + 4,4
C = 5,5 - 3,5
C = 2